Nutrient Requirements of Fish and Shrimp - National Research Council (The National Academies Press, 2011)
Aquaculture now supplies half of the seafood and fisheries products consumed worldwide and is gaining international significance as a source of food and income. Future demands for seafood and fisheries products can only be met by expanded aquaculture production. Such production will likely become more intensive and will depend increasingly on nutritious and efficient aquaculture feeds containing ingredients from sustainable sources.
Keywords: Agriculture

Nutrient Requirements of Swine: Eleventh Revised Edition - National Research Council (The National Academies Press, 2012)
Since 1944, the National Research Council has published 10 editions of the Nutrient Requirements of Swine. This reference has guided nutritionists and other professionals in academia and the swine and feed industries in developing and implementing nutritional and feeding programs for swine. The swine industry has undergone considerable changes since the tenth edition was published in 1998 and some of the requirements and recommendations set forth at that time are no longer relevant or appropriate. The eleventh revised edition of the Nutrient Requirements of Swine builds on the previous editions published by the National Research Council. A great deal of new research has been published during the last 15 years and there is a large amount of new information for many nutrients. In addition to a thorough and current evaluation of the literature on the energy and nutrient requirements of swine in all stages of life, this volume includes information about feed ingredients from the biofuels industry and other new ingredients, requirements for digestible phosphorus and concentrations of it in feed ingredients, a review of the effects of feed additives and feed processing, and strategies to increase nutrient retention and thus reduce fecal and urinary excretions that could contribute to environmental pollution. The tables of feed ingredient composition are significantly updated. Nutrient Requirements of Swine represents a comprehensive review of the most recent information available on swine nutrition and ingredient composition that will allow efficient, profitable, and environmentally conscious swine production.
Keywords: Agriculture

Nutrient Requirements of Beef Cattle: Eighth Revised Edition - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Since 1944, the National Research Council (NRC) has published seven editions of the Nutrient Requirements of Beef Cattle. This reference has guided nutritionists and other professionals in academia and the cattle and feed industries in developing and implementing nutritional and feeding programs for beef cattle. The cattle industry has undergone considerable changes since the seventh revised edition was published in 2000 and some of the requirements and recommendations set forth at that time are no longer relevant or appropriate. The eighth revised edition of the Nutrient Requirements of Beef Cattle builds on the previous editions. A great deal of new research has been published during the past 14 years and there is a large amount of new information for many nutrients. In addition to a thorough and current evaluation of the literature on the energy and nutrient requirements of beef in all stages of life, this volume includes new information about phosphorus and sulfur contents; a review of nutritional and feeding strategies to minimize nutrient losses in manure and reduce greenhouse gas production; a discussion of the effect of feeding on the nutritional quality and food safety of beef; new information about nutrient metabolism and utilization; new information on feed additives that alter rumen metabolism and postabsorptive metabolism; and future areas of needed research. The tables of feed ingredient composition are significantly updated. Nutrient Requirements of Beef Cattle represents a comprehensive review of the most recent information available on beef cattle nutrition and ingredient composition that will allow efficient, profitable, and environmentally conscious beef production.
Keywords: Agriculture

Nutrient Requirements of Dairy Cattle: Eighth Revised Edition - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Since 1944, the National Research Council (NRC) has published seven editions of the Nutrient Requirements of Dairy Cattle. This reference has guided nutritionists and other professionals in academia and the dairy and feed industries in developing and implementing nutritional and feeding programs for dairy cattle. The eighth revised edition of the Nutrient Requirements of Dairy Cattle builds on the previous editions. A great deal of new research has been published and there is a large amount of new information for many nutrients. This book represents a comprehensive review of the most recent information available on efficient, profitable, and environmentally conscious dairy cattle nutrition and ingredient composition.
Keywords: Agriculture

Nutrient Requirements of Dogs and Cats - National Research Council (The National Academies Press, 2006)
Updating recommendations last made by the National Research Council in the mid-1980s, this report provides nutrient recommendations based on physical activity and stage in life, major factors that influence nutrient needs. It looks at how nutrients are metabolized in the bodies of dogs and cats, indications of nutrient deficiency, and diseases related to poor nutrition. The report provides a valuable resource for industry professionals formulating diets, scientists setting research agendas, government officials developing regulations for pet food labeling, and as a university textbook for dog and cat nutrition. It can also guide pet owners feeding decisions for their pets with information on specific nutrient needs, characteristics of different types of pet foods, and factors to consider when feeding cats and dogs.
Keywords: Agriculture; Biology and Life Sciences

Exploring Horizons for Domestic Animal Genomics: Workshop Summary - National Research Council (The National Academies Press, 2002)
Recognizing the important contributions that genomic analysis can make to agriculture, production and companion animal science, evolutionary biology, and human health with respect to the creation of models for genetic disorders, the National Academies convened a group of individuals to plan a public workshop that would: (1) assess these contributions; (2) identify potential research directions for existing genomics programs; and (3) highlight the opportunities of a coordinated, multi-species genomics effort for the science and policymaking communities. Their efforts culminated in a workshop sponsored by the U.S. Department of Agriculture, Department of Energy, National Science Foundation, and the National Institutes of Health. The workshop was convened on February 19, 2002. The goal of the workshop was to focus on domestic animal genomics and its integration with other genomics and functional genomics projects.
Keywords: Biology and Life Sciences

Nutrient Requirements of Nonhuman Primates: Second Revised Edition - National Research Council (The National Academies Press, 2003)
This new release presents the wealth of information gleaned about nonhuman primates nutrition since the previous edition was published in 1978. With expanded coverage of natural dietary habits, gastrointestinal anatomy and physiology, and the nutrient needs of species that have been difficult to maintain in captivity, it explores the impact on nutrition of physiological and life-stage considerations: infancy, weaning, immune function, obesity, aging, and more. The committee also discusses issues of environmental enrichment such as opportunities for foraging.
Keywords: Agriculture; Biology and Life Sciences

Nutrient Requirements of Horses: Sixth Revised Edition - National Research Council (The National Academies Press, 2007)
Proper formulation of diets for horses depends on adequate knowledge of their nutrient requirements. These requirements depend on the breed and age of the horse and whether it is exercising, pregnant, or lactating.
Keywords: Agriculture

Nutrient Requirements of Beef Cattle: Seventh Revised Edition: Update 2000 - National Research Council (The National Academies Press, 2000)
As members of the public becomes more concious of the food they consume and its content, higher standards are expected in the preparation of such food. The updated seventh edition of Nutrient Requirements of Beef Cattle explores the impact of cattle's biological, production, and environmental diversities, as well as variations on nutrient utilization and requirements. More enhanced than previous editions, this edition expands on the descriptions of cattle and their nutritional requirements taking management and environmental conditions into consideration. The book clearly communicates the current state of beef cattle nutrient requirements and animal variation by visually presenting related data via computer-generated models. Nutrient Requirements of Beef Cattle expounds on the effects of beef cattle body condition on the state of compensatory growth, takes an in-depth look at the variations in cattle type, and documents the important effects of the environment and stress on food intake. This volume also uses new data on the development of a fetus during pregnancy to prescribe nutrient requirements of gestating cattle more precisely. By focusing on factors such as product quality and environmental awareness, Nutrient Requirements of Beef Cattle presents standards and advisements for acceptable nutrients in a complete and conventional manner that promotes a more practical understanding and application.
Keywords: Agriculture

Nutrient Requirements of Small Ruminants: Sheep, Goats, Cervids, and New World Camelids - National Research Council (The National Academies Press, 2007)
Updating two previous National Research Council publications, Nutrient Requirements of Sheep, Sixth Revised Edition, 1985, and Nutrient Requirements of Goats, First Edition, 1981, this new book provides an evaluation of the scientific literature on the nutrient requirements of small ruminants in all stages of life. In addition, effects of the environment, feed additives, and metabolism modifiers on nutrient requirements are addressed. Proper formulation of diets for small ruminants depends on adequate knowledge of their nutrient requirements. These requirements depend on the breed and age of the animal and whether he or she is exercising, pregnant, or lactating. Nutrient Requirements of Small Ruminants brings together a summary of this latest data with new and expanded information on the composition of feeds commonly consumed by small ruminants, both domestic and wild. For the first time this authoritative reference work includes information on cervids and camelids. Primarily intended for animal nutritionists, veterinarians, and other scientists, some sections will be useful to individual sheep and goat owners and managers and to those responsible for the care and management of wildlife species. As both a practical and a technical reference book, this material is written to ensure that diets of small ruminants contain adequate amounts of nutrients and that intakes of certain nutrients are not so excessive that they inhibit performance or impair health.
Keywords: Agriculture

Nutrient Requirements of Dairy Cattle: Seventh Revised Edition, 2001 - National Research Council (The National Academies Press, 2001)
This widely used reference has been updated and revamped to reflect the changing face of the dairy industry. New features allow users to pinpoint nutrient requirements more accurately for individual animals. The committee also provides guidance on how nutrient analysis of feed ingredients, insights into nutrient utilization by the animal, and formulation of diets to reduce environmental impacts can be applied to productive management decisions.
Keywords: Agriculture; Food and Nutrition

Microphysiological Systems: Bridging Human and Animal Research: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Microphysiological systems (MPS) are complex, multi-cellular in vitro systems that commonly include three-dimensional aspects, fluid flow, changing pressure or stretch, and multi-organ interactions. These systems are being developed to better mimic some aspects of specific organ systems or combinations of organ systems to improve upon standard two-dimensional cell systems, with the goal of eventually replacing animal models being used for hazard identification, risk assessment, and disease modeling, among other uses. The National Academies of Sciences, Engineering and Medicine convened a workshop to discuss current progress in developing MPS that realistically model in vivo animal and human physiology and to strategize about the potential to establish sustainable human and animal MPS banks. Speakers discussed how MPS fit within the portfolio of tools used in their fields of expertise, the limitations and areas of needed improvement for MPS, and how MPS may be used in the future as the technology develops. This publication summarizes the presentation and discussion of the workshop.
Keywords: Biology and Life Sciences

Animal Welfare Challenges in Research and Education on Wildlife, Non-Model Animal Species and Biodiversity: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Research to advance understanding of the ecology and biology of wildlife species is more important than ever as the world confronts issues ranging from biodiversity loss to the emergence of zoonotic diseases. However, the current understanding of animal welfare in research and education has been based on laboratory work with specific domesticated species. Wildlife research represents a starkly different context and with different implications for animal welfare. Wild species that are the subject of research have extremely diverse physiologies and behaviors and live in diverse habitats. This makes it challenging and sometimes impossible for wildlife researchers to follow the recommendations outlined in the Guide for the Care and Use of Laboratory Animals (NRC 2011) and other guidelines developed for a laboratory-based, biomedically focused research context. To explore issues associated with the unique welfare considerations of wildlife research, the National Academies of Sciences, Engineering, and Medicine (under the auspices of the Roundtable on Science and Animal Welfare in Laboratory Animal Use), hosted a workshop titled Discussing and Understanding Animal Welfare Challenges in Research and Education on Wildlife, Non-Model Animal Species, and Biodiversity on February 9-10, 2022. The event, held virtually, included pre-recorded presentations and overarching discussions to explore this topic in breadth and depth. More than 1,800 participants from academia, industry, government, and nonprofit organizations joined the webcast. This proceedings summarizes key topics covered in the workshop presentations and discussions based on transcripts, recordings, and slides from the event.
Keywords: Biology and Life Sciences

Companion Animals as Sentinels for Predicting Environmental Exposure Effects on Aging and Cancer Susceptibility in Humans: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
To examine the potential role of companion animals as sentinels of relevant, shared environmental exposures that may affect human aging and cancer, the National Cancer Policy Forum held a workshop in collaboration with the Forum on Aging, Disability, and Independence and the Standing Committee on the Use of Emerging Science for Environmental Health Decisions to explore this promising and underutilized pathway for research. Presentations and panel discussions covered the current state of the science and pathways for accelerating research, along with opportunities and challenges for using this novel translational approach to exposure science to advance human health. This Proceedings of a Workshop outlines the presentations and discussions that occurred during the workshop.
Keywords: Health and Medicine; Environment and Environmental Studies

Reproducibility Issues in Research with Animals and Animal Models: Workshop in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
In June 2014, the Roundtable on Science and Welfare in Laboratory Animal Use organized a public workshop to discuss fundamental aspects of experimental design of research using animals and animal models, aimed at improving reproducibility. At this workshop, researchers from around the world explored the many facets of animal-based research that could contribute to irreproducible results, including perspectives on improving experimental planning, design, and execution; the importance of reporting all methodological details; and efforts to establish harmonization principles of reporting on the care and use of animals in research studies.
Keywords: Biology and Life Sciences

Rapid Response by Laboratory Animal Research Institutions During the COVID-19 Pandemic: Lessons Learned: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The National Academies of Sciences, Engineering, and Medicine convened a workshop to explore lessons learned at animal research institutions in response to SARS-CoV-2, the cause of the COVID-19 pandemic. Expert scientists conducting COVID-19 research, as well as institutional leadership responsible for oversight in areas such as, veterinary medical care, occupational health, risk assessment and biosafety, and public messaging and communications presented and participated in panel discussions. This publication summarizes the presentations and discussion of the workshop.
Keywords: Biology and Life Sciences

Report Series: Committee on Planetary Protection: Evaluation of Bioburden Requirements for Mars Missions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Since the 1980s, national and international planetary protection policies have sought to avoid contamination by terrestrial organisms that could compromise future investigations regarding the origin or presence of Martian life. Over the last decade, the number of national space agencies planning, participating in, and undertaking missions to Mars has increased, and private-sector enterprises are engaged in activities designed to enable commercial missions to Mars. The nature of missions to Mars is also evolving to feature more diversity in purposes and technologies. As missions to Mars increase and diversify, national and international processes for developing planetary protection measures recognize the need to consider the interests of scientific discovery, commercial activity, and human exploration. The implications of these changes for planetary protection should be considered in the context of how much science has learned about Mars, and about terrestrial life, in recent years. At the request of NASA, this report identifies criteria for determining locations on Mars potentially suitable for landed robotic missions that satisfy less stringent bioburden requirements, which are intended to manage the risk of forward contamination.
Keywords: Space and Aeronautics

Potential Research Priorities to Inform Public Health and Medical Practice for Domestic Zika Virus: Workshop in Brief - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Given the recent rapid spread of Zika virus (ZIKV) throughout the Americas and the presence of its vector mosquito species within parts of the United States, RADM Nicole Lurie, Assistant Secretary for Preparedness and Response, U.S. Department of Health and Human Services, determined an urgent need for additional research to better characterize ZIKV, especially those issues related to the means of transmission and infection during pregnancy. The National Academies of Sciences, Engineering, and Medicine convened a 1-day public workshop on February 16, 2016, to discuss and explore key factors associated with ZIKV.
Keywords: Health and Medicine

Transportation of Laboratory Animals: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The obligation to treat animals used in research ethically and humanely extends beyond their lives in the laboratory to include their transportation from place to place. Yet transporting animals is a highly regulated and complex process that raises many difficult issues.
Keywords: Biology and Life Sciences

Achieving Nutrient and Sediment Reduction Goals in the Chesapeake Bay: An Evaluation of Program Strategies and Implementation - National Research Council (The National Academies Press, 2011)
The Chesapeake Bay is North America's largest and most biologically diverse estuary, as well as an important commercial and recreational resource. However, excessive amounts of nitrogen, phosphorus, and sediment from human activities and land development have disrupted the ecosystem, causing harmful algae blooms, degraded habitats, and diminished populations of many species of fish and shellfish. In 1983, the Chesapeake Bay Program (CBP) was established, based on a cooperative partnership among the U.S. Environmental Protection Agency (EPA), the state of Maryland, and the commonwealths of Pennsylvania and Virginia, and the District of Columbia, to address the extent, complexity, and sources of pollutants entering the Bay. In 2008, the CBP launched a series of initiatives to increase the transparency of the program and heighten its accountability and in 2009 an executive order injected new energy into the restoration. In addition, as part of the effect to improve the pace of progress and increase accountability in the Bay restoration, a two-year milestone strategy was introduced aimed at reducing overall pollution in the Bay by focusing on incremental, short-term commitments from each of the Bay jurisdictions. The National Research Council (NRC) established the Committee on the Evaluation of Chesapeake Bay Program Implementation for Nutrient Reduction in Improve Water Quality in 2009 in response to a request from the EPA. The committee was charged to assess the framework used by the states and the CBP for tracking nutrient and sediment control practices that are implemented in the Chesapeake Bay watershed and to evaluate the two-year milestone strategy. The committee was also to assess existing adaptive management strategies and to recommend improvements that could help CBP to meet its nutrient and sediment reduction goals. The committee did not attempt to identify every possible strategy that could be implemented but instead focused on approaches that are not being implemented to their full potential or that may have substantial, unrealized potential in the Bay watershed. Because many of these strategies have policy or societal implications that could not be fully evaluated by the committee, the strategies are not prioritized but are offered to encourage further consideration and exploration among the CBP partners and stakeholders.
Keywords: Environment and Environmental Studies; Earth Sciences